Screening of candidate genes encoding proteins expressed in pectoral fins of fugu Takifugu rubripes, in relation to habitat site of parasitic copepod Caligus fugu, using suppression subtractive hybridization - Norshida, Ismail; Satoshi, Tasumi; Geoffrey, A Boxshall (Academic Press, 2015)
Caligus fugu is a parasitic copepod specific to the tetraodontid genus Takifugu including the commercially important Takifugu rubripes. Despite the rapid accumulation of knowledge on other aspects of its biology, the host and settlement-site recognition mechanisms of this parasite are not yet well understood. Since the infective copepodid stage shows preferential site selection in attaching to the fins, we considered it likely that the copepodid recognizes chemical cues released or leaking from the fins, and/or transmembrane protein present on the fins. To isolate molecules potentially related to attachment site specificity, we applied suppression subtractive hybridization (SSH) PCR by identifying genes expressed more highly in pectoral fins of T. rubripes than in the body surface skin. We sequenced plasmid DNA from 392 clones in a SSH library. The number of non-redundant sequences was 276, which included 135 sequences located on 117 annotated genes and 141 located in positions where no genes had been annotated. We characterized those annotated genes on the basis of gene ontology terms, and found that 46 of the identified genes encode secreted proteins, enzymes or membrane proteins. Among them nine showed higher expression in the pectoral fins than in the skin. These could be candidate genes for involvement in behavioral mechanisms related to the site specificity shown by the infective copepodids of C. fugu.